# |
ODE |
Mathematica |
Maple |
\[
{}y^{\prime \prime }-x y-x^{6}-x^{3}+42 = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-x^{2} y-x^{2} = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-x^{2} y-x^{3} = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-x^{2} y-x^{4} = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-x^{2} y-x^{4}+2 = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-2 x^{2} y-x^{4}+1 = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-x^{3} y-x^{3} = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-x^{3} y-x^{4} = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-x^{2} y^{\prime }-x^{2} y-x^{2} = 0
\] |
✗ |
✓ |
|
\[
{}y^{\prime \prime }-x^{3} y^{\prime }-x^{3} y-x^{3} = 0
\] |
✗ |
✗ |
|
\[
{}y^{\prime \prime }-x y^{\prime }-x y-x = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-x^{2} y^{\prime }-x y-x^{2} = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-x^{2} y^{\prime }-x^{2} y-x^{3}-x^{2} = 0
\] |
✗ |
✓ |
|
\[
{}y^{\prime \prime }-x^{2} y^{\prime }-x^{3} y-x^{4}-x^{2} = 0
\] |
✗ |
✓ |
|
\[
{}y^{\prime \prime }-\frac {y^{\prime }}{x}-x y-x^{2}-\frac {1}{x} = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-\frac {y^{\prime }}{x}-x^{2} y-x^{3}-\frac {1}{x} = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-\frac {y^{\prime }}{x}-x^{3} y-x^{4}-\frac {1}{x} = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-x^{3} y^{\prime }-x y-x^{3}-x^{2} = 0
\] |
✗ |
✗ |
|
\[
{}y^{\prime \prime }-x^{3} y^{\prime }-x^{2} y-x^{3} = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-x^{3} y^{\prime }-x^{3} y-x^{4}-x^{3} = 0
\] |
✗ |
✗ |
|
\[
{}y^{\prime \prime }+c y^{\prime }+k y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+y = \sin \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+y = \sin \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+y = \sin \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+y = \sin \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+y = \sin \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+y = \sin \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+y = \sin \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+y = \sin \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+y^{\prime }+y = \sin \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+y^{\prime }+y = \sin \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+y^{\prime }+y = \sin \left (x \right )
\] |
✓ |
✓ |
|
\[
{}x^{4} y^{\prime \prime }+x^{3} y^{\prime }-4 x^{2} y = 1
\] |
✓ |
✓ |
|
\[
{}x^{4} y^{\prime \prime }+x^{3} y^{\prime }-4 x^{2} y = x
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }+x y^{\prime }-4 y = x
\] |
✓ |
✓ |
|
\[
{}\left (x^{2}+1\right ) y^{\prime \prime }+1+{y^{\prime }}^{2} = 0
\] |
✓ |
✓ |
|
\[
{}\left (x^{2}+1\right ) y^{\prime \prime }+1+{y^{\prime }}^{2} = x
\] |
✗ |
✓ |
|
\[
{}\left (x^{2}+1\right ) y^{\prime \prime }+1+x {y^{\prime }}^{2} = 1
\] |
✓ |
✓ |
|
\[
{}\left (x^{2}+1\right ) y^{\prime \prime }+y {y^{\prime }}^{2} = 0
\] |
✗ |
✗ |
|
\[
{}\left (x^{2}+1\right ) y^{\prime \prime }+{y^{\prime }}^{2} = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+\sin \left (y\right ) {y^{\prime }}^{2} = 0
\] |
✓ |
✓ |
|
\[
{}\left (x^{2}+1\right ) y^{\prime \prime }+{y^{\prime }}^{3} = 0
\] |
✓ |
✓ |
|
\[
{}4 x^{2} y^{\prime \prime }+y = 8 \sqrt {x}\, \left (\ln \left (x \right )+1\right )
\] |
✓ |
✓ |
|
\[
{}\frac {x y^{\prime \prime }}{1-x}+y = \frac {1}{1-x}
\] |
✓ |
✓ |
|
\[
{}\frac {x y^{\prime \prime }}{1-x}+x y = 0
\] |
✓ |
✓ |
|
\[
{}\frac {x y^{\prime \prime }}{1-x}+y = \cos \left (x \right )
\] |
✓ |
✓ |
|
\[
{}\frac {x y^{\prime \prime }}{-x^{2}+1}+y = 0
\] |
✗ |
✗ |
|
\[
{}y^{\prime \prime } = \left (x^{2}+3\right ) y
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+20 y^{\prime }+500 y = 100000 \cos \left (100 x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime } \sin \left (2 x \right )^{2}+y^{\prime } \sin \left (4 x \right )-4 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime } = A y^{{2}/{3}}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+2 x y^{\prime }+\left (x^{2}+1\right ) y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+2 \cot \left (x \right ) y^{\prime }-y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }+x y^{\prime }+\left (x^{2}-\frac {1}{4}\right ) y = 0
\] |
✓ |
✓ |
|
\[
{}4 x^{2} y^{\prime \prime }+\left (-8 x^{2}+4 x \right ) y^{\prime }+\left (4 x^{2}-4 x -1\right ) y = 4 \sqrt {x}\, {\mathrm e}^{x}
\] |
✓ |
✓ |
|
\[
{}x y^{\prime \prime }-\left (2+2 x \right ) y^{\prime }+\left (x +2\right ) y = 6 \,{\mathrm e}^{x} x^{3}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+2 y^{\prime }-24 y = 16-\left (x +2\right ) {\mathrm e}^{4 x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+3 y^{\prime }-4 y = 6 \,{\mathrm e}^{2 t -2}
\] |
✓ |
✓ |
|
\[
{}x y^{\prime \prime }-\left (2 x +1\right ) y^{\prime }+\left (1+x \right ) y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+{\mathrm e}^{y} = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime } = 0
\] |
✓ |
✓ |
|
\[
{}{y^{\prime \prime }}^{2} = 0
\] |
✓ |
✓ |
|
\[
{}{y^{\prime \prime }}^{n} = 0
\] |
✓ |
✓ |
|
\[
{}a y^{\prime \prime } = 0
\] |
✓ |
✓ |
|
\[
{}a {y^{\prime \prime }}^{2} = 0
\] |
✓ |
✓ |
|
\[
{}a {y^{\prime \prime }}^{n} = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime } = 1
\] |
✓ |
✓ |
|
\[
{}{y^{\prime \prime }}^{2} = 1
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime } = x
\] |
✓ |
✓ |
|
\[
{}{y^{\prime \prime }}^{2} = x
\] |
✓ |
✓ |
|
\[
{}{y^{\prime \prime }}^{3} = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}{y^{\prime \prime }}^{2}+y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+{y^{\prime }}^{2} = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+y^{\prime } = 1
\] |
✓ |
✓ |
|
\[
{}{y^{\prime \prime }}^{2}+y^{\prime } = 1
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+{y^{\prime }}^{2} = 1
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+y^{\prime } = x
\] |
✓ |
✓ |
|
\[
{}{y^{\prime \prime }}^{2}+y^{\prime } = x
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+{y^{\prime }}^{2} = x
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+y^{\prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}{y^{\prime \prime }}^{2}+y^{\prime }+y = 0
\] |
✗ |
✗ |
|
\[
{}y^{\prime \prime }+{y^{\prime }}^{2}+y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+y^{\prime }+y = 1
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+y^{\prime }+y = x
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+y^{\prime }+y = 1+x
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+y^{\prime }+y = x^{2}+x +1
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+y^{\prime }+y = x^{3}+x^{2}+x +1
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+y^{\prime }+y = \sin \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+y^{\prime }+y = \cos \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+y^{\prime } = 1
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+y^{\prime } = x
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+y^{\prime } = 1+x
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+y^{\prime } = x^{2}+x +1
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+y^{\prime } = x^{3}+x^{2}+x +1
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+y^{\prime } = \sin \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+y^{\prime } = \cos \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+y = 1
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+y = x
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+y = 1+x
\] |
✓ |
✓ |
|